2018
DOI: 10.1364/ol.43.002607
|View full text |Cite
|
Sign up to set email alerts
|

Near ground measure and theoretical model of plane wave covariance of intensity in anisotropic turbulence

Abstract: Experimental measurements were recently made which displayed characteristics of plane wave propagation through anisotropic optical turbulence. A near-plane wave beam was propagated a distance of 1 and 2 km at a height of 2 m above the concrete runway at the Shuttle Landing Facility, Kennedy Space Center, Florida, during January and February of 2017. The spatial-temporal fluctuations of the beam were recorded, and the covariance of intensity was calculated. These data sets were compared to a theoretical calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…A similar measurement campaign obtained the intensity covariance function of a plane wave propagating in the vicinity of a runway (2 km path, 2 m above the ground) [38]. As Figure 4 illustrates, a more precise anisotropy structure was revealed in which both positive and negative correlations are seen.…”
Section: Anisotropic Turbulencementioning
confidence: 88%
“…A similar measurement campaign obtained the intensity covariance function of a plane wave propagating in the vicinity of a runway (2 km path, 2 m above the ground) [38]. As Figure 4 illustrates, a more precise anisotropy structure was revealed in which both positive and negative correlations are seen.…”
Section: Anisotropic Turbulencementioning
confidence: 88%
“…Although the Kolmogorov turbulence model is the most widely utilized atmospheric turbulence model at present Andrews and Phillips [1], as more and more atmospheric experimental results inconsistent with the Kolmogorov turbulence model are discovered, scientists have found that the anisotropic non-Kolmogorov turbulence model is a more realistic model for atmospheric turbulence Manning [2]; Procaccia and Constantin [3]; Belen'kii et al [4]; Toselli et al [5]; Andrews et al [6]; Kessar et al [7]; Cui et al [8]; Wang et al [9]; Beason et al [10]; Zhai [11]; Roşu et al [12]; Xu and Lai [13,14]. Later, in the process of establishing the anisotropic non-Kolmogorov turbulence model and related turbulence theory, in order to simplify the modeling, a hypothesis that the long axis of the turbulence cell should be horizontal to the ground is extensively introduced Andrews et al [6]; Cui et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the Kolmogorov turbulence model being currently the most generally used atmospheric turbulence model [1], as more and more atmospheric experimental results violate the Kolmogorov turbulence model, scholars have discovered that the anisotropic non-Kolmogorov turbulence model is more consistent with the actual situation of atmospheric turbulence [2][3][4][5][6][7][8]. The investigation on light wave transmission in anisotropic non-Kolmogorov atmospheric turbulence has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…So far almost all anisotropic non-Kolmogorov turbulence models established by scholars are based on the assumption that the long axis of turbulence cell should be horizontal to the ground. However, the results of recent experiments by Wang et al and Beason et al have obviously demonstrated that the turbulence cell has an anisotropic tilt angle, i.e., the long axis of turbulence cell may not be horizontal to the ground but has a certain angle with the ground [7,8]. Thus, it is vital to derive the anisotropic non-Kolmogorov turbulence spectra for the horizontal and satellite links with anisotropic tilt angle.…”
Section: Introductionmentioning
confidence: 99%